After and Before the Lightning - Ortiz, Simon J., 1941- (Book collections on Project MUSE., 1994)
The weather--portrayed with vivid imagery--dominates this collection, set on the prairies. In Three Days Before Spring, Snow Again, he writes: "Wind is up again, / swirling and pushing around / like it had nowhere to go, / losing and finding things / and losing them again." By the author of Woven Stone.